Literature review bayi berat lahir rendah - Sujianti, Sujianti (Poltekkes Kemenkes Yogyakarta, 2017)
Indonesia is one of the developing countries with the highest maternal mortality and infant. The infant mortality cases in 2015 asmany as 33,278 cases decreased compared to the year 2015 of 32,007 and in 2017 in the first semester as many as 10,294 cases.One of the causes is the incidence of Low Birth Weight (LBW) of 38.85%. LBW is the birth weight less than 2,500 grams. The reviewof LBW is done by literature review from DOAJ, Pubmed, Scholar and Garuda portal. The literature search using several keywords is